Mexican immigrants in meatpacking areas of Kansas: transition and acquisition of cultural capital - Aguilar R., Daniel E. (Kansas State University, 2008)
A number of cities in Kansas have experienced rapid growth in Hispanic population during the last twenty five years, due to immigration related in particular to the development of the meatpacking industry in the region. Garden City, Dodge City, and Liberal in southwest Kansas and Emporia in eastern Kansas have undergone significant transformation due to the influx of immigrants, the large majority of whom are of Mexican background. The present research approaches these immigrants from a sociological perspective, observing their cultural characteristics in order to understand who they are, and the process they face when adapting to the receiving environment, as a process of acquisition of cultural capital (Bourdieu 1977). This study focuses on the elements from Midwestern culture that are adopted and adapted, as well as the elements from the immigrants' cultural backgrounds that are softened or modified in order to fit within the receiving environment. The study examines these processes, from the theoretical perspective modeled by Pierre Bourdieu, as an attempt to develop an interpretive and comprehensive approach of immigrant experiences.
Keywords: Mexican Immigrants; Cultural Capital; Kansas; Immigration; Sociology, Ethnic and Racial Studies (0631); Sociology, General (0626)